Resting-State fMRI Study of ADHD and Internet Gaming Disorder. Issue 8 (June 2021) - Han, Doug Hyun; Bae, Sujin; Hong, Jisun; Kim, Sun Mi; Son, Yong Don; Renshaw, Perry
Objective: We aimed to understand whether Attention Deficit Hyperactivity Disorder (ADHD) and Internet gaming disorder (IGD) share similar brain functional connectivity (FC) between the frontal and subcortices.Method: We compared changes in clinical symptoms and brain activity using functional magnetic resonance imaging (fMRI) in 26 patients with ADHD but without IGD, 29 patients with ADHD and IGD, and 20 patients with IGD but without ADHD.Results: The functional connectivity (FC) from the cortex to subcortex in both groups was decreased relative to that in age-matched healthy participants. One-year treatment for ADHD and IGD symptoms increased the FC between the cortex and subcortex in all ADHD participants and all IGD participants with good prognoses compared with those in all ADHD participants and all IGD participants with poor prognoses.Conclusion: Patients with ADHD and IGD shared similar brain FC at baseline and FC changes in response to treatment.